Supply Chain Management: Putting the end customer first. - Harrison, Alan; Godsell, Janet (Cranfield University, 2003)
This paper explores aspects of alignment in the supply chain by extending the boundaries of operations management theory into the supply chain. Instead of a focus on manufacturing processes in isolation, the paper proposes that a broader, supply-chain view of alignment with product characteristics in the market place needs to be undertaken. Our views are illustrated by a case study that investigated the European 3PL operation involving the supply, sortation and despatch of parts and subassemblies for a manufacturer we have called ElecCo. Flexible capabilities had been developed – unnecessarily in our view – in order to cope with the high variability of demand placed on the supply chain by ElecCo’s desire to provide the stock market with higher priority than the end cus